2023
DOI: 10.1038/s41598-023-33762-3
|View full text |Cite
|
Sign up to set email alerts
|

The chromosome-scale genome assembly of cluster bean provides molecular insight into edible gum (galactomannan) biosynthesis family genes

Abstract: Cluster bean (Cyamopsis tetragonoloba (L.) Taub 2n = 14, is commonly known as Guar. Apart from being a vegetable crop, it is an abundant source of a natural hetero-polysaccharide called guar gum or galactomannan. Here, we are reporting a chromosome-scale reference genome assembly of a popular cluster bean cultivar RGC-936, by combining sequencing data from Illumina, 10X Genomics, Oxford Nanopore technologies. An initial assembly of 1580 scaffolds with an N50 value of 7.12 Mb was generated and these scaffolds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The transcriptome sequences of S. multipunctatus were compared with BLASTP (Evalue < 1 × 10 −5 ) to find conserved paralog sequences to detect polypoidization events in the transcriptome of S. multipunctatus. Protein sequences of Ctenopharyngodon idellus, Cyprinus carpio, Carassius auratus, and three Sinocyclocheilus species were also analyzed and used for comparison using the WGDdetector software (https://github.com/yongzhiyang2 012/wgddetector, accessed on 12 January 2023) [37], which has shown high performance in detecting recent and ancient WGD events; for example, it was applied in the study of WGD events of Lautoconus ventricosus [38], Xenopus laevis [37], and Cyamopsis tetragonoloba [39]. The protein and CDS sequences within each gene family were automatically compared using MAFFT [40] and PAL2NAL [29], and assigned the corresponding Ks values to each pair of similar sequences (gap-stripped comparison length > 90 bp) within each gene family based on the Nei-Gojobori algorithm.…”
Section: Detection Of Polyploidization Eventsmentioning
confidence: 99%
“…The transcriptome sequences of S. multipunctatus were compared with BLASTP (Evalue < 1 × 10 −5 ) to find conserved paralog sequences to detect polypoidization events in the transcriptome of S. multipunctatus. Protein sequences of Ctenopharyngodon idellus, Cyprinus carpio, Carassius auratus, and three Sinocyclocheilus species were also analyzed and used for comparison using the WGDdetector software (https://github.com/yongzhiyang2 012/wgddetector, accessed on 12 January 2023) [37], which has shown high performance in detecting recent and ancient WGD events; for example, it was applied in the study of WGD events of Lautoconus ventricosus [38], Xenopus laevis [37], and Cyamopsis tetragonoloba [39]. The protein and CDS sequences within each gene family were automatically compared using MAFFT [40] and PAL2NAL [29], and assigned the corresponding Ks values to each pair of similar sequences (gap-stripped comparison length > 90 bp) within each gene family based on the Nei-Gojobori algorithm.…”
Section: Detection Of Polyploidization Eventsmentioning
confidence: 99%
“…Transcription factors function as transcriptional regulation of gene expression, which is crucial to the plant's response to various abiotic and biotic stresses [64,65]. In Astragalus sinicus, functional insight of WGD retained genes showed they were also related to plant hormone signal transduction, accompanied by plant-pathogen interaction [66].…”
Section: Gene Duplicationsmentioning
confidence: 99%
“…It has been found that hormones are crucial in the process of nodulation [66]. Therefore, WGD shared by legume species could contribute to the hormonal regulation of nodulation.…”
Section: Gene Duplicationsmentioning
confidence: 99%
“…It is grown in India for vegetable, green manure and seed production. It is also recognized as a medicinal plant and possesses a high quantity of phytochemicals [19,20]. It is commonly used to cure various diseases like ulcer, secretion, hyperglycemia, and cathartic [21].…”
Section: Introductionmentioning
confidence: 99%